SENI KRIYA DAYAK DALAM KANCAH INDUSTRI - Wasita, Wasita (Naditira Widya, 2008)
Proverb:life goes on constant change is inevitable; therefore, it is necessary to transfer distinguish values of the continuously-fading-Dayak-legacy by revitalizing and presenting the Dayak craftsmanship into the life of the present day Dayak. The Dayak craft will be founded on industrial-cultural-based consept to uplift the Dayak distinguish value to reinforce their cultural identity and honor, and be able to open up entrepreneurship possibilities. Similar transfer may be also applied delivering education, unity, and bestowing finance. This article discusses strategic possibility to transfer distinguish values and simultaneously reinforce the Dayaks cultural identity and honor in forms of souvenirs production.